Chapter 5. Population viability - Santos, Jorge (Septentrio Educational, 2015)
This chapter of CONΣERV IT deals with the following questions in aquatic conservation: - What is conservation biology? - Do fish populations get extinct or extirpated? - Is it bad that related populations rescue each other? Extirpation